Monetary policy and financial stability: Cross-country evidence - Christian Friedrich; Kristina Hess; Rose Cunningham (Bank of Canada, 2015)
Central banks may face challenges in achieving their price stability goals when financial stability risks are present. There is, however, considerable heterogeneity among central banks with respect to how they manage these potential trade-offs. In this paper, we review the institutional and operational policy frameworks of ten central banks in major advanced economies and then assess the effect of financial stability risks on their monetary policy decisions according to these frameworks. To do so, we construct a timevarying financial stability orientation (FSO) index that quantifies a central bank's policy orientation with respect to financial stability that spans the major viewpoints of the literature: "leaning against the wind" versus "cleaning up after the crash." The index encompasses three dimensions: (i) the nature of the statutory frameworks, (ii) the extent of the regulatory tool kit, and (iii) the prominence of financial stability references in central bank monetary policy statements. We then include our FSO index in a modified Taylor rule, which is estimated using a cross-country panel of up to ten central banks for the period from 2000Q1 to 2014Q4. We find that in episodes of high financial stability risks, measured by a strongly positive credit to GDP gap, "leaning-type" central banks, i.e., those with a high FSO index value, appear to account for financial stability considerations in their monetary policy rate decisions. For "cleaning-type" central banks, we do not find this to be the case. Our baseline specification suggests that a representative leaning-type central bank's policy rate is about 0.3 percentage points higher when financial stability risks are present than the policy rate of a representative cleaning-type central bank. We also find that the strength of this response increases in the additional presence of a house price boom but not so for the simultaneous occurrence of an equity price boom.
Keywords: E5; E4; G01; 330; Monetary policy framework; Financial stability; International topics